Recent records of marine mammals in Tanzanian waters - Amir , Omar A.; Berggren, Per; Jiddawi, Narriman S. (J. Cetacean Res. Manage., 2023)
Marine mammal species diversity off Zanzibar and Tanzania, East Africa, has been recorded by the Marine Mammal Education and Research Group at the Institute of Marine Sciences, Zanzibar, Tanzania since 1998. The data presented in this report reflect the efforts of 10 years collection of information from marine mammals stranded and incidentally caught in Tanzanian waters. Additional information from dedicated surveys of cetaceans (whales and dolphins) and incidental sightings reported by the general public are also provided. From 1992 through 2008 a total of 235 specimens of 13 cetacean species and the dugong were recorded. 214 (90.7%) records referred to specimens from bycatch in drift and bottom-set gillnets and 22 (9.3%) referred to specimens from strandings. Based on incidental catch and sightings records, Indo-Pacific bottlenose, spinner and Indo-Pacific humpback dolphins, observed year-round, and humpback whales, observed seasonally during July to November, were the most common species in Tanzanian coastal waters.